Determinants of default from completion of child immunization among children aged 15–23 months in Kacha Bira district, Kembata Tembaro zone, South Ethiopia: a case–control study - Masebo, Sitota Tesema; Wolka, Eskinder; Kussa, Sintayehu; Uloro, Muluken Markos; Handiso, Selamu Abera; Libabo, Dilugeta Mathewos; Anjajo, Eyosiyas Abreham; Bogino, Efa Ambaw (Frontiers in Public Health, 2024)
Background Child immunization is crucial to protect children from vaccine-preventable diseases. However, if a child defaults from completing immunization, they are at a greater risk of contracting such diseases. Previous studies have evaluated various factors that contribute to defaulting from immunization, but they did not consider the fear of COVID-19 as a variable. Additionally, there is inconsistency in the factors identified across different areas. This study aimed to examine the determinants of defaulting from child immunization among children aged 15–23 months in Kacha Bira district, Kembata Tembaro zone, South Ethiopia. Methods A study was conducted using a community-based unmatched case–control design to identify the determinants of child immunization completion. The study included 255 children aged 15–23 months in the Kacha Bira district from 3 May 2022 to 1 June 2022, using a multi-stage sampling technique. Face-to-face interviews of mothers or immediate caretakers of the child were conducted using a mobile device, and the questionnaire was developed using the Kobo Toolbox. The data collected were analyzed using SPSS version 25. Multivariable logistic regression was used to identify the determinants, and the adjusted odds ratio with 95% CI and a p < 0.05 were considered statistical significant. Results The multivariable logistic regression analysis identified four independent predictors of immunization defaulting. Antenatal care (ANC) follow-up [AOR = 5.40, 95% CI (2.24–13.52)], postponing vaccination schedule [AOR = 2.28, 95% CI: (1.05–4.93)], parity of the mother [AOR = 3.25, 95% CI: (1.45–7.27)], and knowledge of the mother about vaccination [AOR = 6.77, 95% CI: (2.33–19.64)] were determinants of immunization defaulting. Conclusion In this study, lack of ANC follow-up, postponement of the vaccination schedule, mothers with parity of greater than four, and poor knowledge of the mothers about immunization were identified as determinants of immunization defaulting.